Public subsidisation of higher education and educational inequality in Malaysia - Bakar, Rosni (Universiti Utara Malaysia, 1999)
The paper examines the relationship between the public subsidy to schooling and educational access in Malaysia. Not many studies have been done on related areas, thus the present study relies heavily on methods used by Psacharopoulos (1977a) and Ram (1982). Using the Gini index and the educational inequality index in the form of the coefficient of variation of student enrolment at three levels of education, it has been possible to assess the influence of public subsidization of higher education on the inequality of educational opportunity access in Malaysia. The findings of this study suggests that subsidization at the second (secondary) and the third level (university) of public education in Malaysia does reduce inequality in educational access to higher education.